Impact of the Chlorination of Lithium Argyrodites on the Electrolyte/Cathode Interface in Solid-State Batteries - Zuo, Tong-Tong; Walther, Felix; Teo, Jun Hao; Rueß, Raffael; Wang, Yubo; Rohnke, Marcus; Schröder, Daniel; Nazar, Linda F.; Janek, Jürgen; Justus Liebig University Giessen (My University, 2023)
Lithium argyrodite-type electrolytes are regarded as promising electrolytes due to their high ionic conductivity and good processability. Chemical modifications to increase ionic conductivity have already been demonstrated, but the influence of these modifications on interfacial stability remains so far unknown. In this work, we study Li6PS5Cl and Li5.5PS4.5Cl1.5 to investigate the influence of halogenation on the electrochemical decomposition of the solid electrolyte and the chemical degradation mechanism at the cathode interface in depth. Electrochemical measurements, gas analysis and time-of-flight secondary ion mass spectrometry indicate that the Li5.5PS4.5Cl1.5 shows pronounced electrochemical decomposition at lower potentials. The chemical reaction at higher voltages leads to more gaseous degradation products, but a lower fraction of solid oxygenated phosphorous and sulfur species. This in turn leads to a decreased interfacial resistance and thus a higher cell performance.
Keywords: ddc:540